The inhibitory effectiveness of ethanol extract of selasih leaves towards Streptococcus sanguis growth - Susilo, Ivhatry Rizky Octavia Putri; Satari, Mieke Hemiawati; Setiawan, Ame Suciati (Padjadjaran Journal of Dentistry, 2015)
Introduction: Selasih is one of tropical and subtropical plant used as traditional medicine. It has antibacterial activity especially toward Gram-positive bacteria because it contains volatile oils, tannin, flavonoid and tertepenoid. Method: The study was performed as an experimental laboratory study used Kirby Bauer agar diffusion applied to eight samples of Streptococcus sanguis which was done by twice repetition for each sample. The concentrations of ethanol extract were 16%, 8%, 4%, 2% and 1%.The result was analysed using ANOVA method for single factor of experimental design. The result of the study showed that there was evidence of the antibacterial effect contained in the ethanol extract of selasih leaves inhibiting the growth of Streptococcus sanguis . The average of inhibitory zone for each concentration in every sample, were: 5,25 mm for 16%, 3,22 mm for 8%, 1,84 mm for 4%, 1,53 mm for  2% and 0,19 mm for 1%. The conclusion of the study indicates that there is an antibacterial effects in ethanol extract of selasih leaves (Ocimum basilicum Linn) which inhibits the growth of Streptococcus sanguis. This antibacterial strength is caused by the active content of selasih leaves extract.Conclusion: The extract of basilicum ethanol (Ocimum basilicum L) effectively inhibits the growth of Streptococcus sanguis.